Tradisi Perkawinan Ana Ale di Desa Tiwu Tewa Kecamatan Ende Timur Kabupaten Ende di Tinjau dari Hukum Adat (Pusat Riset dan Inovasi Nasional, 2026)
One of the long-standing marriage traditions in the Ende community is the ana ale marriage tradition. Ana ale marriage is a form of marriage based on an agreement between the parents of the man and woman, as well as a long-established good relationship between both parents. This research was conducted in Tiwu Tewa Village, Ende Timur District, Ende Regency. This research aims to understand the fundamental values contained in marriage as viewed from customary law, the process of implementation and its legitimacy, as well as the obstacles in the implementation of the ana ale marriage. The method used is empirical legal research with a qualitative approach, which includes interviews and literature study. The research results show that the fundamental values contained in the ana ale marriage, as viewed from customary law, consist of sacred and spiritual values, responsibility and commitment values, social and mutual assistance values, and adherence to customs. The process of implementing the ana ale marriage includes Ru’u Tu Jaga Rara, Janji, Puzi Ru’u, Teo Zambu, Bou Engga, Mai Tu Gega Padha, Tu Ngawi, Teke Ngara, Dari Nikah, Tu Ana. Meanwhile, the marriage is considered valid at the Tu Ana ceremony. The obstacles faced in the ana ale marriage include economic factors and the occurrence of clandestine marriages by the female party.